POM-QM Utilization On Healthcare-Utensils Demand Identification And Distribution In Indonesia - Mohammad Annas; Humairoh Humairoh; Veera Pandiyan Kaliani Sundram; Siti Norida Wahab (Cita Konsultindo Research Center, 2023)
The study aims at healthcare utensils and the most accurate solutions to healthcare-utensils distributed by major logistics providers in Indonesia. The fast-moving utensils the logistics providers had identified are then being treated as a priority process and must be delivered to the intended region fulfillment possible due to the high urgency of the fulfillment. The study occurred in five capital cities of Indonesia, where those logistics providers operated. Primary and secondary data were used to support the analysis, and the methodology of procurement forecasting was implemented to support the research recommendations. The analysis was done by implementing features of POM-QM, particularly the feature of forecasting methods. The result showed that fluctuating demands and procurement of healthcare utensils gave huge problems to logistics providers as they had to arrange the transporter and its schedule in advance. Only one method, the linear trend line, with the least value of MAD, MSE, and MAPE below 5%, was found suitable to measure and anticipate the demands of healthcare utensils. Unfortunately, this method was never done by the logistics providers during the pandemic due to a loss of knowledge and insights into statistical methodologies.